The importance of supportive leadership in the sewerage operation industry in Malaysia: A case of Indah Water Konsortium Private Limited (IWK) - Ayu Suriawaty Bahkia; Zainudin Awang; Nor Azma Rahlin; Mohamad Zulkifli Abdul Rahim (Maya Global Education Society, 2020)
Purpose: This study intends to determine the importance of Supportive Leadership in the sewerage operation industry since the nature of work itself, together with workload and pressure, has resulted in severe occupational stress among the workers; consequently, it would translate into poor work commitment. Methodology: The random sample was obtained from the sampling frame, which consists of employees of the sewerage operation company in Malaysia, namely, Indah water Konsortium (IWK). Data was gathered using a self-administered questionnaire given to the randomly selected respondents. Meanwhile, data were analyzed using the second-generation method of multivariate analysis called Structural Equation Modeling (SEM) in IBM-SPSS-AMOS 24.0. Furthermore, the results were reconfirmed through bootstrapping procedures. Result: The study found Supportive Leadership fully mediates the relationship between Occupational Stress and Work Commitment. The finding of this research indicates that in this particular industry, Supportive Leadership is extremely important to transform from negative Work Commitment to positive and significant Work Commitment from the employees. Applications: The management of sewerage operation industries needs to be supportive of their workers in order to obtain a positive and significant commitment from the workers amid the work pressure and stress. Novelty/Originality: Unlike other industries, the sewerage operation industry (in Malaysia) is pre-occupied with work burden and under tremendous work pressure. The study that links occupational stress and work commitment are scarce, especially in this particular industry, and in developing countries like Malaysia.